Multi-Motor Octagonal Blender Drive - Roopa Nayak, Dr. Andhe Pallavi (International Journal of Advanced Science and Technology, 2020)
Blenders and mixers play a vital role in cosmetic, packaged food, pharmaceutical industries, where they are used for mixing the raw ingredients. Blending is carried out for a fixed duration and at a controlled fixed speed. The ingredient blending is a major factor that contributes greatly to the quality of the final product. One such blender employed in pharmaceutical industries for tablet making is octagonal blender. These blenders are powered by motor-drive arrangements. To ensure reliability, standby motors are stocked up to keep downtime as low as possible. Using dual motors of lower power rating, would call for stocking up a lower power rating motor, thereby reducing space and additional cost of maintenance of standby motor. The quantity of raw mix that can be blended at a time depends on the capacity of the blender container and in turn depends on the motor rating that powers the blender. Hence, the blending process is carried out in batches. The processing time can be brought down if larger quantity of raw mix can be blended in each batch. This can be achieved by incorporating dual motors to power the blender in the scenario of mass production. This paper proposes to replace an existing single motor-drive arrangement for an octagonal blender by dual motor-drive arrangements of smaller ratings. Both the existing and the proposed systems are modelled and simulated in MATLAB/SIMULINK and their performance is discussed.